Citizens assemble: a study on the impact of climate reporting in the Irish media 'before', 'during' and 'after' the Citizens' Assembly on 'how the state can make Ireland a leader in tackling climate change'. Issue 2 (3rd April 2021) - McGovern, Rhonda; Thorne, Peter
ABSTRACT: The Citizens' Assembly, a form of deliberative mini-public, tasked 99 ordinary Irish citizens with the responsibility of deliberating on five topics, after which they made recommendations to government. Throughout assembly meetings members were presented with up-to-date accurate information from experts. 'How the State can make Ireland a leader in tackling climate change' was considered third by the assembly over two weekends. On the final day the citizens voted on thirteen strongly endorsed recommendations for government to act on. The release of the final report in April 2018 saw a further four ancillary recommendations added. There was considerable media coverage surrounding the Citizens' Assembly for this topic. This research undertakes a content analysis of four national media sources over fifteen-months; the Farmers Journal, the Irish Independent, The Irish Times and TheJournal.ie . We found that climate related reporting became more neutral in tone and more divergent in its relationship to evidence over the research period. There was a reflection of the key themes from the Citizens' Assembly in each media source, and themes changed through time for each publication. Two of the media sources examined increased their overall levels of climate reporting while the other two decreased.